Fast Software Encryption 15th International Workshop, FSE 2008, Lausanne, Switzerland, February 10-13, 2008, Revised Selected Papers - Nyberg, Kaisa (Security and Cryptology, 2008)
This book constitutes the thoroughly refereed proceedings of the 15th International Workshop on Fast Software Encryption, FSE 2008, held in Lausanne, Switzerland in February 2008. The 26 revised full papers presented together with 4 short papers were carefully reviewed and selected from 72 submissions. The papers address all current aspects of fast and secure primitives for symmetric cryptology and are organized in topical sections on SHA collisions, new hash function designs, block cipher cryptanalysis, implementation aspects, hash function cryptanalysis, stream cipher cryptanalysis, security bounds, and entropy.